„Czasy ginącego piękna”. Pozytywistycznej historii literatury kłopoty z barokiem - Szewczyk-Haake, Katarzyna (My University, 2012)
The article deals with the ways in which Baroque works and their authors were presented in the positivist history of literature. The source material for the analysis was provided by the texts written by Piotr Chmielowski, Stanisław Tarnowski, Adam Bełcikowski, Henryk Sienkiewicz and Felicjan Faleński. The article discusses the sources for a rather distinct dislike of the literary output of Baroque authors in general, which was in line with the then well-established opinions deeply rooted in European research, but also derived from a valuation based on national and patriotic criteria. A certain differentiation in research methods is also indicated, mostly of those stemming from the spirit of Taine, but, occasionally, approaching Baroque works with the help of a stylistic analysis and thus making it possible to show more appreciation to the literature created in the period that, as understood from the positivist perspective, was believed to be of inferior quality.
“The Period of Disappearing Beauty”. A Problem with Baroque of Positivistic History of Literature
Keywords: positivist history of literature; Baroque; taine; valuation in literary studies